The effect on group reflection on nursing students' spiritual well-being and attitude toward spiritual care: A randomized controlled trial - Marzieh Momennasab; Zahra Shadfard; Azita Jaberi; Seyed Saeed Najafi; Fakhrozaman Naeemi Hosseini (Universidad de Antioquia, 2019)
Objective. To investigate how group reflection about spiritual care affects nursing students' spiritual well-being and attitude toward spirituality and spiritual care. Methods. This was a randomized controlled trial conducted on 63 second-year nursing students who were studying at Nursing and Midwifery Colleges in Shiraz and Jahrom, both located in south of Iran. The students were randomly divided into an intervention (n=30) and a control (n=33) group. The study data were collected using the Spiritual Well-Being Scale and Spirituality and Spiritual Care Rating Scale before and after the intervention. The intervention consisted in four sessions of group reflection based on the scenarios related to spiritual care. The control group was given a related lecture in one session. Results. A significant difference was found between the two groups' means in spiritual well-being scores after the intervention compared to before that. Likewise, a significant difference was observed in the intervention group students' total scores of attitude before and after the intervention. Conclusion. Group reflection improved the nursing students' spiritual well-being and their attitude toward spirituality and spiritual care compared with control group.   How to cite this article: Momennasab M, Shadfard Z, Jaberi A, Najafi SS, Hosseini FN. The Effect of Group Reflection on Nursing Students' Spiritual Well-being and Attitude Toward Spiritual Care: a randomized controlled trial. Invest. Educ. Enferm. 2019; 37(1):e09.